Effect of neutron exposure on structural and optical properties of tailor-made Gd-Doped SiO2 glass. (November 2021) - Ismail, S.S.; Abdul Sani, S.F.; Khandaker, M.U.; Tamchek, N.; Ridzuan, C.M.; Karim, Julia A.; Almugren, K.S.; Alkallas, F.H.; Bradley, D.A.
Abstract: The effect of neutron irradiation is investigated in respect of five different Gd dopant concentrations of silica (SiO2 ) glass; 1–10 mol% via sol-gel route fabrication. Using Raman spectroscopy and X-ray diffraction (XRD), characterization was made of the defects that give rise to the luminescence signal. The approach allows the Si–O–Si coordination to be identified and studied. The fabrication process as well as irradiation have been found to produce defects which influence the luminescence response of the material. The Raman spectra from Gd-doped SiO2 glass neutron irradiated to doses from 2 to 10 Gy show five prominent peaks (at 300, 430, 680, 820, 1050 cm −1 ) with the presence of Gd-O-Gd seen at 300 cm −1 . The Miller index (211) crystal plane observed from XRD allowed calculation of the atomic spacing, lattice constant and degree of structural order of the irradiated samples. The results show that from fabrication of silica of different Gd dopant concentration and the effect of neutron irradiation these lead to a number of desirable characteristics for use of the medium as a dosimetric system for neutron radiation physics applications. Highlights: Sol gel glass doped with Gd at 1–10 mol% concentration irradiated to neutron source. Change in lattice structure and defect upon exposure to neutron radiation. Gd-O-Gd bond is found to be at 300 cm −1 Raman band. Si–O–Si bond are found to be at 430, 680, 820 and 1050 cm −1 Raman band. The doping support an increase in amorphous.